MoFap7, a ribosome assembly factor, is required for fungal development and plant colonization of Magnaporthe oryzae. Issue 1 (1st January 2019) - Li, Lin; Zhu, Xue-Ming; Shi, Huan-Bin; Feng, Xiao-Xiao; Liu, Xiao-Hong; Lin, Fu-Cheng
ABSTRACT: Fap7, an important ribosome assembly factor, plays a vital role in pre-40S small ribosomal subunit synthesis in Saccharomyces cerevisiae via its ATPase activity. Currently, the biological functions of its homologs in filamentous fungi remain elusive. Here, MoFap7, a homologous protein of ScFap7, was identified in the rice blast fungus Magnaporthe oryzae, which is a devastating fungal pathogen in rice and threatens food security worldwide. Δ Mofap7 mutants exhibited defects in growth and development, conidial morphology, appressorium formation and infection, and were sensitive to oxidative stress. In addition, site-directed mutagenesis analysis confirmed that the conserved Walker A motif and Walker B motif in MoFap7 are essential for the biological functions of M. oryzae . We further analyzed the regulation mechanism of MoFap7 in pathogenicity. MoFap7 was found to interact with MoMst50, a regulator functioning in the MAPK Pmk1 signaling pathway, that participates in modulating plant penetration and cell-to-cell invasion by regulating the phosphorylation of MoPmk1. Moreover, MoFap7 interacted with the GTPases MoCdc42 and MoRac1 to control growth and conidiogenesis. Taken together, the results of this study provide novel insights into MoFap7-mediated orchestration of the development and pathogenesis of filamentous fungi.